2016
DOI: 10.1002/anie.201608515
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatible Polymer Grafting from Individual Living Cells by Atom‐Transfer Radical Polymerization

Abstract: A cytocompatible method of surface-initiated, activator regenerated by electron transfer, atom transfer radical polymerization (SI-ARGET ATRP) is developed for engineering cell surfaces with synthetic polymers. Dopamine-based ATRP initiators are used for both introducing the ATRP initiator onto chemically complex cell surfaces uniformly (by the material-independent coating property of polydopamine) and protecting the cells from radical attack during polymerization (by the radical-scavenging property of polydop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 46 publications
2
97
0
Order By: Relevance
“…As shown in Figure 3c,y east@MnO 2 revealed 80 %v iability versus 10 % for the native yeast, verifying the enhanced cellular resistance against harmful H 2 O 2 provided by these MnO 2 shells.Avery recent study demonstrated that polydopamine shells could process temporary protection against radical attack during the polymerization but lacked long-term efficacy. [10] Thus,we assessed the long-term preservation capability of these shells by incubating yeast@MnO 2 together with toxic H 2 O 2 for 48 h. Excitingly,over 65 %ofyeast@MnO 2 remained viable under such an extreme condition versus 5% for the native yeast (Figure 3d), suggesting that the robust nanozyme shells were effective in continuously removing toxic chemicals for prolonged cell survival while also protecting the cellular structure from dehydration. Besides,the durable shells could also be served as an enhanced safeguard to protect living cells against multiple stressors,such as lethal lytic enzyme and UV radiation, which were additionally tested and verified in detail ( Figure S14 and Figure S15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3c,y east@MnO 2 revealed 80 %v iability versus 10 % for the native yeast, verifying the enhanced cellular resistance against harmful H 2 O 2 provided by these MnO 2 shells.Avery recent study demonstrated that polydopamine shells could process temporary protection against radical attack during the polymerization but lacked long-term efficacy. [10] Thus,we assessed the long-term preservation capability of these shells by incubating yeast@MnO 2 together with toxic H 2 O 2 for 48 h. Excitingly,over 65 %ofyeast@MnO 2 remained viable under such an extreme condition versus 5% for the native yeast (Figure 3d), suggesting that the robust nanozyme shells were effective in continuously removing toxic chemicals for prolonged cell survival while also protecting the cellular structure from dehydration. Besides,the durable shells could also be served as an enhanced safeguard to protect living cells against multiple stressors,such as lethal lytic enzyme and UV radiation, which were additionally tested and verified in detail ( Figure S14 and Figure S15).…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the preservation of cell viability and functionality in harsh environments,the single cell encapsulation technique has exhibited its potential in am ultiplicity of fields,s uch as biocatalysis,cell-based sensors,and therapy. [1][2][3][4] Va rious coating shells including silica (SiO 2 ), [5,6] calcium phosphates (CaP), [7] polymers, [8][9][10] as well as metal coordination complexes [11,12] have been widely exploited to shield cells from hostile stressors and external environments.D espite the potential advantages of above protective coatings,t he practical utilization of these shells in real systems still remains problematic.F irstly,t hese coatings usually provide limited protection against molecular toxic chemicals,s uch as H 2 O 2 , owing to their intrinsic inertness and permeability.A fter rapidly equilibrating across the shells,t oxic chemicals can ultimately induce the death of cells. [13][14][15] Secondly,t hese coating shells can only be decomposed by treatment with some harmful compounds,including HCl and EDTA, indicating the further impossibility of non-invasive control of cell functions and single cell based biology.…”
mentioning
confidence: 99%
“…Another disadvantage is that the ATRP reaction has to be conducted in a completely inert atmosphere, which would further complicate the process. The above drawbacks can be overcome by using activators regenerated by electron transfer ATRP (ARGET‐ATRP) . The key of this process is the introduction of an excess reducing agent which minimizes the copper catalyst to ppm level.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled radical polymerization (CRP; e.g., atom‐transfer radical polymerization (ATRP) and reversible addition‐fragmentation chain‐transfer polymerization (RAFT)) has particularly been used for cell‐surface engineering because of its advantageous characteristics including low concentration of radicals and low cross‐reactivity of biological functional groups. The potential cytotoxicity of free radicals, generated from initiators and monomers during CRP, was minimized further in two reported approaches . In one approach, a radical‐protective layer of PD‐based macroinitiators was formed on yeast cell surfaces, and then a mild version of ATRP (activators regenerated by electron transfer ATRP, ARGET ATRP) in an aqueous solution was conducted (Figure b).…”
Section: Progresses In Synthetic Strategies For “Cell‐in‐shell” Strucmentioning
confidence: 99%
“…In one approach, a radical‐protective layer of PD‐based macroinitiators was formed on yeast cell surfaces, and then a mild version of ATRP (activators regenerated by electron transfer ATRP, ARGET ATRP) in an aqueous solution was conducted (Figure b). [27a] The radical‐scavenging property of PD greatly increased the cell viability after SI‐ARGET ATRP, forming “yeast‐in‐polymer” structures.…”
Section: Progresses In Synthetic Strategies For “Cell‐in‐shell” Strucmentioning
confidence: 99%